The influence of mesoscale climate drivers on hypoxia in a fjord-like deep coastal inlet and its potential implications regarding climate change : examining a decade of water quality data - Johnathan Daniel, Maxey; Neil David, Hartstein; Aazani, Mujahid; Moritz, Müller (Copernicus Publications on behalf of the European Geosciences Union., 2022)
Deep coastal inlets are sites of high sedimentation and organic carbon deposition that account for 11 % of the world’s organic carbon burial. Australasia’s mid- to highlatitude regions have many such systems. It is important to understand the role of climate forcings in influencing hypoxia and organic matter cycling in these systems, but many such systems, especially in Australasia, remain poorly described.